Photocrosslinkable Gelatin Hydrogels Modulate the Production of the Major Pro-inflammatory Cytokine, TNF-α, by Human Mononuclear Cells - Donaldson, Amy R.; Tanase, Constantin Edi; Awuah, Dennis; Vasanthi Bathrinarayanan, Pranav; Hall, Laurence; Nikkhah, Mehdi; Khademhosseini, Ali; Rose, Felicity; Alexander, Cameron; Ghaemmaghami, Amir M. (Frontiers in Bioengineering and Biotechnology, 2018)
Hydrogels are an attractive class of biomaterials in tissue engineering due to their inherently compatible properties for cell culture. Gelatin methacryloyl (GelMA) has shown significant promise in the fields of tissue engineering and drug delivery, as its physical properties can be precisely tuned depending on the specific application. There is a growing appreciation for the interaction between biomaterials and cells of the immune system with the increasing usage of biomaterials for in vivo applications. Here, we addressed the current lack of information regarding the immunogenicity of photocrosslinked GelMA. We investigated the ability of human mononuclear cells to mount inflammatory responses in the context of a GelMA hydrogel platform. Using lipopolysaccharide to stimulate a pro-inflammatory immune response, we found tumour necrosis factor-α (TNF-α) expression was suppressed in GelMA culture conditions. Our findings have important implications on the future use of GelMA and highlight the significance of investigating the potential immune-modulatory properties of biomaterials.